Exploring configurations of social determinants for enhancing older adult health in China: an fuzzy-set qualitative comparative analysis based on 31 provinces in China - Zhang, Songbiao; Wang, Xining; Wang, Huilin (Frontiers in Public Health, 2023)
With China’s aging population on the rise, addressing population aging has become a national priority, particularly focusing on improving older adult health. This study employs the social determinants of health framework, considering China’s unique macro-social, economic, policy, healthcare, and family cultural factors, to develop a framework for understanding the social determinants of health for older adult in China. Using the fsQCA method and a configurational perspective, the complex relationship between social determinants of health and older adult health status is examined. The findings indicate that individual social determinants alone are insufficient for achieving high levels of older adult health. Instead, three configurations of social determinants have been identified as conducive to high older adult health: Economic Development-Environment – Cultural Dominant Type, Socio-Economic Development – Older Adult Security – Environment – Cultural Dominant Type, and Economic Development Dominant Type. These configurations offer diverse pathways for enhancing older adult health. Conversely, the study identifies two configurations associated with low older adult health levels, exhibiting an asymmetric relationship with the configurations resulting in high older adult health levels. Moreover, economic development consistently emerges as a core condition across all three configurations associated with high older adult health levels, while two configurations associated with low older adult health lack this core condition. These findings underscore the universal contribution of enhancing economic development to improving older adult health.